Academic Qualification and Teachers’ Job Satisfaction in Secondary Schools in Nakuru County-Kenya - Maina, Margaret; Kiumi, J Kanjogu; Githae, Peter (International Journal of Educational Studies, 2021)
Teacher job satisfaction is one of the critical determinants of the rate of progress in students learning outcomes. The teaching profession in Kenya has in the recent past experienced industrial disharmony by way of teachers’ strikes, which could be a pointer to dissatisfaction among teachers. Teacher dissatisfaction is typically rooted in failure by entities responsible for teacher management to meet teachers’ needs. Research-based evidence demonstrates that employees have different needs and that these needs are influenced by factors such as employee’s level of training or education for that matter. Drawing on these observations, the study sought to determine whether an academic qualification has any bearing on teachers’ job satisfaction in secondary schools in Nakuru County, Kenya. Data was collected using a self-delivered questionnaire from 341 teachers who were randomly selected from 3,092 teachers in the study locale. The instrument’s validity and reliability as estimated through split-half and Cronbach’s alpha stood at r=.945 and r=.905 respectively. Collected data was analyzed using ANOVA statistic at .05 alpha level. A major finding of the study was that teacher satisfaction decreased with an increase in the level of academic qualification. Qualification–differentiated satisfaction was also statistically significant (p<.05). The study offers useful insights to the Teachers Service Commission (TSC) and school managers on how to enhance teachers’ job satisfaction by way of addressing the needs of teachers in different levels of academic qualification.